2021
DOI: 10.1177/1099800420985615
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Relationships Between Health Behaviors and IL-6 in Overweight and Obese Pregnancy

Abstract: Background: Inflammation is a common factor in adverse pregnancy outcomes (APOs). Behavioral factors influence inflammatory markers and APOs but rarely have been investigated simultaneously in pregnancy. Our purpose was to determine how diet, physical activity, and obesity are associated with interleukin (IL)-6 in early and late pregnancy. Methods: We conducted a secondary analysis of 49 overweight/obese pregnant women. Health behavior data, including diet quality using the Dietary Inflammatory Index (DII®); p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…These findings are consistent with the limited available literature. In a longitudinal study of 49 women with overweight and obesity by Wallace et al, the E-DII TM did not change from early to late pregnancy [ 3 ]. The PEARs antenatal lifestyle intervention was not designed to reduce inflammation but rather to reduce the glycaemic potential of the diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with the limited available literature. In a longitudinal study of 49 women with overweight and obesity by Wallace et al, the E-DII TM did not change from early to late pregnancy [ 3 ]. The PEARs antenatal lifestyle intervention was not designed to reduce inflammation but rather to reduce the glycaemic potential of the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests the association between pre-pregnancy overweight and obesity and adverse maternal and foetal outcomes is mediated through inflammation [ 2 ]. Early pregnancy diet and weight may have implications for inflammation throughout pregnancy [ 3 ]. In addition, emerging evidence suggests that maternal inflammation during pregnancy may impact foetal neurodevelopment, possibly with long-term effects [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, gestational weight gain was 40 % in obese mothers, compared to lean mothers. Although several studies have shown that maternal obesity is associated with an inflammatory and pro-oxidant milieu [47,48], there are reports of healthy obese mothers with no signs of dyslipaemia [13,49]. On the other hand, irrespective of its severity, there are consistent data showing that several placental responses appear to be affected by maternal pre-gestational obesity [16,50].…”
Section: Discussionmentioning
confidence: 99%